Screening dan Pendidikan Kesehatan tentang Resiko Jatuh pada Lansia di RW VI Dukuh Persen Kelurahan Sekaran - Achmad Syaifudin; Sumarno Sumarno; Ayu Dita Handayaningtyas; Komsiyah Komsiyah; Dian Nur Kumalasari; Fhandy Aldy Mandaty; Alfiyah Alfiyah (Pusat Riset dan Inovasi Nasional, 2024)
Aging results in a decreased ability of tissues to regenerate, which is a natural and unavoidable process. Physical changes in the elderly often limit their independence in performing daily activities, thus increasing the risk of falls. The aim of this activity is to conduct screening and interventions in the form of education on fall prevention, risk factors for falls, methods of preventing falls, and balance exercises for the elderly. The methods used in this activity include lectures and Q&A sessions. The results showed that 11 elderly participants (43%) were at high risk of falling and 15 elderly participants (57%) were at low risk of falling. Some complaints from the elderly related to the risk of falling include frequent dizziness when getting up from a lying position, difficulty walking due to stiffness/joint pain, and trouble sleeping soundly. To reduce the risk of falls in the elderly, health services that include aspects of prevention, treatment, and collaboration, such as health education and balance exercise assistance, are needed.